(untitled) (Anclajes, 2020)
Images can activate or deactivate violence and have important political value, so analyzing their implications is essential. In this article we will investigate the representative forms of violence against women and racialized, impoverished bodies located in the Global South, specifically in Colombia and Mexico, through two recent films: La mujer del Animal (2016), directed by Víctor Gaviria, and Backyard: El traspatio (2009), directed by Carlos Carrera and written by Mexican playwright and feminist Sabina Berman. We will use an interdisciplinary methodology in which feminist film theory and critical discourse analysis intersect in order to propose a transfeminist methodology of encryption and re-codification of the images of violence, so they do not give up their role as social criticism.